COMMENTARY: WHAT HEALS AND WHY? CHILDREN'S UNDERSTANDING OF MEDICAL TREATMENTS. Issue 2 (18th April 2018) - Rosengren, Karl S.; Jiang, Matthew J.; Kalish, Charles W.; Menendez, David; Hernandez, Iseli G.
Abstract : Lockhart and Keil have written an interesting monograph focusing on the development of reasoning about medicine, a relatively underexplored area of research with potentially broad implications with respect to the design of more‐effective medical interventions. In a set of 15 studies with well over 2, 200 participants, they examine how children and adults combine aspects of biological and psychological reasoning to create working models of medicine. Lockhart and Keil explore developmental changes in reasoning about illness and its treatment using medicines in terms of dualism (e.g., psychological vs. physical), spatial proximity, differential timing of effects, potential side effects, and treatment tradeoffs. This commentary highlights the novel contributions of this monograph, examines issues that need additional considerations, and makes suggestions for future research.